Phosphoinositide 5-phosphatases SKIP and SHIP2 in ruffles, the endoplasmic reticulum and the nucleus: An update. (January 2020) - Ramos, Ana Raquel; Ghosh, Somadri; Suhel, Tara; Chevalier, Clément; Obeng, Eric Owusu; Fafilek, Bohumil; Krejci, Pavel; Beck, Benjamin; Erneux, Christophe
Abstract: Phosphoinositides (PIs) are phosphorylated derivatives of phosphatidylinositol. They act as signaling molecules linked to essential cellular mechanisms in eukaryotic cells, such as cytoskeleton organization, mitosis, polarity, migration or invasion. PIs are phosphorylated and dephosphorylated by a large number of PI kinases and PI phosphatases acting at the 5-, 4- and 3- position of the inositol ring. PI 5-phosphatases i.e. OCRL, INPP5B, SHIP1/2, Synaptojanin 1/2, INPP5E, INPP5J, SKIP (INPP5K) are enzymes that dephosphorylate the 5-phosphate position of PIs. Several human genetic diseases such as the Lowe syndrome, some congenital muscular dystrophy and opsismodysplasia are due to mutations in PI phosphatases, resulting in loss-of-function. The PI phosphatases are also up or down regulated in several human cancers such as glioblastoma or breast cancer. Their cellular localization, that is dynamic and varies in response to stimuli, is an important issue to understand function. This is the case for two members of the PI 5-phosphatase SKIP and SHIP2. Both enzymes are in ruffles, plasma membranes, the endoplasmic reticulum, a situation that is unique for SKIP, and the nucleus. Following localization, PI 5-phosphatases act on specific cellular pools of PIs, which in turn interact with target proteins. Nuclear PIs have emerged as regulators of genome functions in different area of cell signaling. They often localize to nuclear speckles, as do several PI metabolizing kinases and phosphatases. We asked whether SKIP and SHIP2 could have an impact on nuclear PI(4, 5)P2. In two glioblastoma cell models, lowering SKIP expression had an impact on nuclear PI(4, 5)P2. In a model of SHIP2 deletion in MCF-7 cells, no change in nuclear PI(4, 5)P2 was observed. Finally, we present evidence of an anti-tumoral role of SKIP in vivo, in xenografts using as model U87shSKIP cells.